P0343 Influence of Intestinal Ultrasound Versus CT enterography on Surgical Strategy Planning of Crohn’s Disease in urgent setting - A D Guarino; G Luglio; L Camera; A Rispo; F P Tropeano; A Testa; O M Nardone; A Zoretti; L Sommella; G Calabrese; L Bonacci; C Leo; et al. (Journal of Crohn’s and Colitis, 2026)
Abstract Background Intestinal ultrasound (IUS) and CT-enterography (CTE) are accurate diagnostic modalities in Crohn’s disease (CD), but their role in surgical planning for complicated cases in urgent settings has not been fully established. This study aims to evaluate the diagnostic accuracy of IUS–CTE and the impact on surgical planning in patients with complicated CD requiring urgent intervention. Methods We conducted a prospective study including CD cases urgently hospitalized between 2022 and 2025 who underwent surgery due to bowel complications. Each patient underwent both IUS/CTE within 3 days, with surgical intervention within 1 month. Diagnostic accuracy was assessed by comparing imaging findings with intraoperative observations, considered as the reference standard. Surgeons were asked to define their intended surgical approach based on both IUS–CTE findings. The concordance between IUS- and CTE-guided strategies was assessed using Cohen’s kappa (κ) coefficient. The differential impact on surgical decision-making was quantified using the Number Needed to Diagnose ratio. Statistical analyses were performed using SPSS software, with p-values < 0.05 considered statistically significant. Results A total of 51 cases were enrolled (behavior B1–B2–B3: 3–31–17; location: L1–L2–L3–L4: 14–1–36–0; prior surgery: 25 cases). All patients underwent bowel resection. Stricturoplasty was performed in 4 cases, and a temporary stoma was required in 4. For the detection of strictures, IUS demonstrated a sensitivity of 78%, specificity of 100%, positive predictive value (PPV) of 100%, negative predictive value (NPV) of 55%, with a diagnostic accuracy of 82%. CTE had a sensitivity of 100%, specificity of 90%, PPV of 97%, NPV of 100%, and an accuracy of 98%. About abscess detection, IUS achieved 100% sensitivity and specificity; CTE demonstrated 100% sensitivity, 95% specificity, 67% PPV, 100% NPV, and an accuracy of 96%. For the detection of fistulas, IUS had a sensitivity of 78%, specificity of 100%, PPV of 100%, and NPV of 92%. CTE showed a sensitivity of 72%, specificity of 96%, PPV of 92%, NPV of 86%, and a diagnostic accuracy of 88%. In terms of surgical planning, IUS influenced the strategy in 64% of cases, compared with 76% for CTE (NND ratio: 19%), with agreement between the two modalities (κ = 0.72; p < 0.01). The discrepancies were observed in defining the extent of resection, particularly among patients with extensive-multifocal involvement. Surgeons considered the 19% NND ratio and 28% disagreement rate between IUS- and CTE-guided surgical strategies as clinically significant for operative decision-making. Conclusion IUS-CTE are accurate imaging modalities for detecting complications in CD.CTE provides a significant advantage over IUS in guiding surgical planning during the preoperative diagnostic work-up of cases urgently admitted with complicated CD. References: 1. Kucharzik T, Tielbeek J, Carter D, Taylor SA, Tolan D, Wilkens R, Bryant RV, Hoeffel C, De Kock I, Maaser C, Maconi G, Novak K, Rafaelsen SR, Scharitzer M, Spinelli A, Rimola J. ECCO-ESGAR Topical Review on Optimizing Reporting for Cross-Sectional Imaging in Inflammatory Bowel Disease. J Crohns Colitis. 2022 May 10;16(4):523-543. doi: 10.1093/ecco-jcc/jjab180. PMID: 34628504. 2. Pruijt MJ, de Voogd FAE, Montazeri NSM, van Etten-Jamaludin FS, D’Haens GR, Gecse KB. Diagnostic Accuracy of Intestinal Ultrasound in the Detection of Intra-Abdominal Complications in Crohn’s Disease: A Systematic Review and Meta-Analysis. J Crohns Colitis. 2024 Jun 3; 18 (6): 958-972. doi: 10.1093/ecco-jcc/jjad215. PMID: 38173288; PMCID: PMC11147796. 3. Verdalle-Cazes M, Charpentier C, Benard C, Joly LM, Dacher JN, Savoye G, Savoye-Collet C. Abdominopelvic CT-scan in emergency departments for patients with suspected complications of Crohn’s disease: a single tertiary center experience. BMC Emerg Med. 2021 Oct 7; 21 (1): 113. doi: 10.1186/s12873-021-00512-5. PMID: 34620106; PMCID: PMC8496012. 4. Bartlett DJ, Ramos GP, Fletcher JG, Bruining DH. Imaging Evaluation of Inflammatory Bowel Disease Complications. Gastrointest Endosc Clin N Am. 2022 Oct; 32 (4): 651-673. doi: 10.1016/j.giec.2022.05.001. Epub 2022 Sep 7. PMID: 36202508. 5. Bettenworth D, Bokemeyer A, Baker M, Mao R, Parker CE, Nguyen T, Ma C, Panés J, Rimola J, Fletcher JG, Jairath V, Feagan BG, Rieder F; Stenosis Therapy and Anti-Fibrotic Research (STAR) Consortium.. Assessment of Crohn’s disease-associated small bowel strictures and fibrosis on cross-sectional imaging: a systematic review. Gut. 2019 Jun; 68 (6): 1115-1126. doi: 10.1136/gutjnl-2018-318081. Epub 2019 Apr 3. PMID: 30944110; PMCID: PMC6580870. Conflict of interest: Dr. Guarino, Alessia Dalila: No conflict of interest Luglio, Gaetano: No conflict of interest Camera, Luigi: No conflict of interest Rispo, Antonio: No conflict of interest Tropeano, Francesca Paola: No conflict of interest Testa, Anna: Consultant /Advisory board for Abbvie, J & J, Takeda, Ferring Nardone, Olga Maria: Advisory board fees from Eli Lilly, Nestlè, Janssen Speaker fees from AbbVie, Janssen, Eli Lilly, Ferring, Alfa Sigma, Recordati, Noòs, and Pfizer Zoretti, Aniello: No conflict of interest Sommella, Laura: No conflict of interest Calabrese, Giulio: Travel grant by Johnson and Johnson Speaker fee by Celltrion Bonacci, Livio: No conflict of interest Leo, Camilla: No conflict of interest Palumbo, Flavia: No conflict of interest Orabona, Chiara: No conflict of interest Petolicchio, Martina: No conflict of interest Castiglione, Fabiana: Honoraria from: Takeda, AbbVie, Celltrion, Johnsson Johnsson, Cadigroup, Sandoz, Pfizer, Lilly, Lionhealth, Nestlè